A comparative analysis of flipped, online and traditional teaching: A case of female Middle Eastern management students. Issue 2 (July 2018) - Fadol, Yasir; Aldamen, Husam; Saadullah, Shahriar
Abstract: This study compares performance and perception of students in a management course at a business school in the Middle East. 122 students completed an Introduction to Management course, which was divided into three different delivery modes, namely traditional, online and flipped. The results of the study reveal several interesting findings. Both the online and flipped sections performed better than the traditional one and the flipped section performed better than the online one. Absenteeism was higher in the traditional mode compared to the flipped mode. Furthermore, accessing online material improved performance in the online and flipped modes; students who accessed the online material missed fewer classes in the flipped mode; and 52% of the students (of whom 58% were high performers) believe the flipped mode is more helpful than the traditional mode. Implications of the study and avenues for future research are discussed. Highlights: Both online and flipped sections performed better than traditional one and flipped section performed better than online one. Accessing online material helped students in the flipped and online modes improve their performance. Students who access online material in the flipped and online modes outperform those who do not. Student absenteeism is higher in the traditional mode compared to the flipped mode. Students believe the flipped mode is more helpful in learning and increase interaction with the instructor and other students.